Functionally graded structures of refractory metals by Wire Arc Additive Manufacturing - Marinelli, Gianrocco; Martina, Filomeno; Ganguly, Supriyo; Williams, Stewart W.; Lewtas, Heather; Hancock, David (Maney Publishing, 2019)
Functionally graded components are usually preferred for severe and critical service conditions, thanks to the possibility of achieving different complementary material properties within the same structure. Wire + Arc Additive Manufacturing is an emerging technology which lends itself well to the production of sound graded structures. In this study, an integral structure of two functional gradients, namely tantalum to molybdenum, and molybdenum to tungsten, was successfully deposited. A linear gradient was observed in both composition and hardness. Microstructure, elemental composition and hardness were characterised as a function of position, and discussed. The study demonstrates that WAAM has the potential to successfully deposit functionally graded structures of refractory metals, obtaining controlled properties
Keywords: WAAM; additive manufacturing; functionally graded structure; refractory metals; refractory metals; microstructure; hardness; chemical analysis